Rethinking Taxation in the Digital Economy - Emerson S. Ba\~nez (Philippine Institute for Development Studies (PIDS), 2022)
The study aims to evaluate the country's legal framework for taxing digital transactions. Specifically, the extent to which the provisions of the law can map onto the value of digital markets. Based on the findings on the structure of the digital commerce value chain, and its possible interactions with both current and proposed tax regimes, four policy prescriptions are recommended. First, to optimize existing tax authority over platforms. Second, to have a digital-ready tax administration. Third, to have an expanded scope for investigation and liability. Finally, to have an engagement at the international level. Non-resident providers are the ones that have gained the most from digital markets while minimizing the tax impact of their activities. The Philippines should continue to explore multilateral options for the reallocation of taxing rights as well addressing BEPS. These include regional tax treaties and the OECD framework treaty. Efforts at negotiating and crafting the provisions should take into account the Philippines' trading power relative to other countries, and its comparative ability to exercise jurisdiction.
Keywords: 330; digital taxation; taxes; digital commerce; tax law; tax administration